Analisis Dampak Pembangunan Jalur Kereta Api Lintas Makassar-Parepare Terhadap Lingkungan Sekitarnya Di Kabupaten Barru - Jayanti, Nadya Eka; Badrun, Burhanuddin; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Transportation is a problem that has an important influence in people's lives. The problem that occurs in transportation in the Makassar-Parepare crossing is the increasing population growth along with the increasing number of users of land transportation modes that are not proportional to public awareness to switch to using public transportation. One of the government's efforts to overcome these problems is the development of rail-based land transportation modes. This research aims to find out the problems that occur in Barru Regency, the factors that cause and the reasons for choosing the train transportation mode and analyze the impact of the construction of the Makassar-Parepare Railway line in Barru Regency. This research uses a qualitative method with a study of relevant literature regarding the impact of the construction of the Makassar-Parepere railway line which is then used as a question on the questionnaire and distributed to the community in the surrounding location, then analyzed using the help of Statistical Package for The Social Sciences software. The results of the study obtained the impact during the implementation of the construction of the railway line on the environment resulted in flooding, economic conditions resulted in decreased agricultural land production, social conditions made residents feel uncomfortable. The impact after the operation of the railway line felt by residents for environmental conditions is reduced congestion, economic conditions reduce local labor, and social conditions many resident roads access is covered by the railway body which makes communication between residents disrupted.